Guidelines for the management of transfusion dependent thalassaemia (TDT) - Cappellini, Maria-Domenica; Cohen, Alan, 1946-; Porter, John (Hematologist); Taher, Ali.; Viprakasit, Vip.; Thalassaemia International Federation (Nicosia (CY) : Thalassaemia International Federation, 2014)
The full costs of treating patients with inherited disorders of haemoglobin is extremely variable among countries depending on different health care systems, varying methods of obtaining blood, different practices in screening for blood pathogens and different costs of drugs and equipment. It is evident that all countries would benefit from the sharing of experience and expertise in order to harmonize and optimize the quality of treatment as much as possible. The need for management guidelines for Transfusion Dependent Thalassaemias (TDT) is clear. Throughout the past four years, six major TDT management guidelines became available for use by thalassaemia care givers (TIF, US, Canadian, UK, Italian and Australian Guidelines). A comparison among those guidelines has been recently published (Musallam KM et al. Acta Haematologica 2013). In light of a swiftly evolving evidence, the need for revisiting and updating TDT management recommendations remains crucial. More importantly, ensuring access to such guidelines and careful application and implementation should only help arriving at early diagnosis of morbidity to allow prompt and effective management. It would also allow early prediction of risk and would enable preventive measures to be set in place saving unnecessary health care costs. This updated third edition of the TIF guidelines will offer valuable information to all allied healthcare professionals involved in the treatment of patients with TDT. It includes updated information on new approaches for more effective, safe and less laborious treatment, and an overview of the progress achieved to date towards a total cure using methods such as gene therapy and stem cell transplantation.
Title from Bookshelf entry page.
Description based on version viewed May 1, 2015.
This freely accessible collection of books may include only specific chapters of some books.
Keywords: Thalassemia -- therapy; Thalassemia -- complications; Blood Transfusion; Internationality; Electronic books